Evaluating public and private partnership to improve food and language nutrition among children 0-5 years - Chinwe Ejikeme; Kia Powell-Threets; Emily Vall; Laura Wagner; Luke Fiedorowicz; Audrey Idaikkadar; Jean O'Connor (Georgia Southern University, 2016)
Background: Racial and ethnic minority populations in Georgia experience increased rates of chronic disease and poor health and education outcomes, which can be prevented through enhanced public- private partnerships. Using the Centers for Disease Control and Prevention (CDC) evaluation framework, the Evaluation Subcommittee for the Georgia Partnership for Food and Language Nutrition Project comprised of representatives from various stakeholders affiliated with state agencies, academia, and community-based organizations developed an evaluation plan to improve the collaborative effort designed to improve food and language nutrition among children 0-5 years. The purpose of this mixed-methods study was to assess influential collaborative factors. Methods: An online assessment survey that included open-ended qualitative questions was administered to all stakeholders (n=15; response rate=67%) to assess the strengths and weaknesses of the partnership, its leadership effectiveness and partners' perceptions about the partnership. Baseline descriptive statistics were calculated and content analysis was performed with the qualitative data to understand partners' perceptions. Results: The partnership scored variably across four categories that determine partnership strengths. Five factors were identified as the strengths of the partnership: favorable political and social climate; members see collaboration as in their self interest; unique purpose of partnership mission and goals; skilled leadership; and sufficient resources to support its operation.However, other areas were found to need urgent intervention, including improving on the leadership of the Georgia Department of Public Health (GA-DPH). In addition, communication as well as process and structure factors were identified as weaknesses including: a need to establish informal relationships and develop communication skills; a lack of flexibility; and an absence of clear roles and policy guides. Conclusions: Developing an action plan to address identified weaknesses will help ensure the accomplishment of the expected health and education outcomes among targeted, minority Georgia communities.